2022
DOI: 10.1007/s11145-022-10256-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of transcription and executive functions in writing: a longitudinal study in the transition from primary to intermediate Grades

Abstract: Learning to write is one of the great challenges children face in primary grades, requiring both transcription skills (handwriting and spelling) and executive functions (EFs; working memory, inhibitory control, and cognitive flexibility). Although this claim is widely accepted, the field suffers from some limitations, including few longitudinal studies examining the joint role of transcription and EFs in the writing of school-age children. The current study aimed to fill in this gap with a twofold goal: to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This suggests that the transfer effect of working memory updating training is more pronounced in early childhood and school-age children. This view is indirectly supported by studies based on tracking primary school students showing that working memory is consistently a significant predictor of writing ability at the primary school stage (Guan et al, 2019 ; Rocha et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that the transfer effect of working memory updating training is more pronounced in early childhood and school-age children. This view is indirectly supported by studies based on tracking primary school students showing that working memory is consistently a significant predictor of writing ability at the primary school stage (Guan et al, 2019 ; Rocha et al, 2022 ).…”
Section: Discussionmentioning
confidence: 94%
“…In this task, students were asked to copy a 9‐word sentence as quickly as possible, without making mistakes, for 90s (Limpo et al, 2018). As in previous studies (e.g., Limpo et al, 2018, 2020; Rocha et al, 2022), the sentence used was ‘O rouxinol azul fugiu do jardim porque chovia bastante’ (‘The blue nightingale ran away from the garden because it rained a lot’). The final score was the number of words accurately copied, with higher scores indicating greater handwriting fluency.…”
Section: Methodsmentioning
confidence: 99%
“…Empirically, substantial studies have indicated the effect of EF on writing performance (e.g., Drijbooms et al, 2015; Hooper et al, 2002; McCutchen, 1996; Rocha et al, 2022; Swanson & Berninger, 1996; Vanderberg & Lee Swanson, 2007). It has been suggested that students’ overall EF performance accounted for 8% to 26.5% variance in writing performance (Arán Filippetti & Richaud, 2015; Balioussis et al, 2012; Drijbooms et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been suggested that students’ overall EF performance accounted for 8% to 26.5% variance in writing performance (Arán Filippetti & Richaud, 2015; Balioussis et al, 2012; Drijbooms et al, 2015). Longitudinal studies (e.g., Cordeiro et al, 2020; Rocha et al, 2022) have also obtained significant contribution of EF to primary school students’ written text quality. Additionally, different EF components may play different roles in writing.…”
Section: Literature Reviewmentioning
confidence: 99%